Analisa Pengaruh Luas Penampang Penghantar dan Cuaca Terhadap Rugi Daya Akibat Korona Pada SUTT 150 kV (Studi Kasus: Gardu Induk Bangkalan – Gardu Induk Sampang) - Ibnu Hajar; Tito Dias Fernando (Energi & Kelistrikan, 2019)
PT. PLN (PERSERO) as a state-owned company responsible in the electricity sector is required to improve the quality of electricity transmission. In the transmission of electrical power to consumers will be got losses of power. Raising the voltage is an alternative to this problem but it creates new problems because the higher the voltage has increased the corona will occur. The impact of the corona in addition to damaging equipment, noise, and disturbing radio waves, the corona also causes power losses that are proportional to the length of the transmission line. This study uses a quantitative method, by calculating the corona power losses by comparing 4 different cross-sectional areas of the conductor and 4 different air temperatures. The results of this study found that the smaller the cross-sectional area of the conductor the power losses due to corona are smaller, conversely the greater the cross-sectional area the greater the power losses. At the smallest cross-sectional area of 282.6 mm2, the power losses that occurred were 2.013% and at the largest cross-sectional area of 378.7 mm2, the power losses were 5.251%. While the influence of air temperature, the lowest corona losses occur at 29 0C which are 1,223,886 kW and the biggest occur at 24 0C which are 1,373,419 kW, so the higher the air temperature the smaller the corona losses, conversely the lower the air temperature than the higher the corona losses that occur.